Exogenous Ketone Supplementation Decreased the Lipopolysaccharide-Induced Increase in Absence Epileptic Activity in Wistar Albino Glaxo Rijswijk Rats - Kovács, Zsolt; D'Agostino, Dominic P.; Diamond, David M.; Ari, Csilla (Frontiers in Molecular Neuroscience, 2019)
It has been demonstrated previously that exogenous ketone supplements, such as ketone ester (KE) decreased absence epileptic activity in a well-studied animal model of human absence epilepsy, Wistar Albino Glaxo/Rijswijk (WAG/Rij) rats. It is known that lipopolysaccharide (LPS)-generated changes in inflammatory processes increase absence epileptic activity, while previous studies show that ketone supplements-evoked ketosis can modulate inflammatory processes. Thus, we investigated in the present study whether administration of exogenous ketone supplements, which were mixed with standard rodent chow (containing 10 % KE + 10 % ketone salt/KS, % by weight, KEKS) for 10 days can modulate the LPS-evoked changes in absence epileptic activity in WAG/Rij rats. At first, KEKS food alone was administered and changes in spike-wave discharge (SWD) number, SWD time, discharge frequency within SWDs, blood glucose and beta-hydroxybutyrate (βHB) levels, as well as body weight and sleep-waking stages were measured. In a separate experiment, intraperitoneal (i.p.) injection of LPS (50 µg/kg) alone and a cyclooxygenase 1 and 2 (COX-1 and COX-2) inhibitor indomethacin (10 mg/kg) alone, as well as combined i.p. injection of indomethacin with LPS (indomethacin + LPS) were applied in WAG/Rij rats to elucidate their influences on SWD number. In order to determine whether KEKS food can modify the LPS-evoked changes in SWD number, KEKS food in combination with i.p. LPS (50 µg/kg) (KEKS + LPS), as well as KEKS food with i.p. indomethacin (10 mg/kg) and LPS (50 µg/kg) (KEKS + indomethacin + LPS) were also administered. We demonstrated that KEKS food significantly increased blood βHB levels and decreased not only the spontaneously generated absence epileptic activity (SWD number), but also the LPS-evoked increase in SWD number in WAG/Rij rats. Our results suggest that administration of exogenous ketone supplements (ketogenic foods) may be a promising therapeutic tool in the treatment of epilepsy.